ALTERNATIF PENYELESAIAN SENGKETA ANTARA MASYARAKAT DENGAN PEMERINTAH TERHADAP KAWASAN HUTAN - Nazia Nazia; Resty Agustin; Tia Agustina; Fedro Rialdo; M. Dava Rizki Saputra; M. Novrianto; Ledy Wila Yustini (Universitas Muhammadiyah Palembang, 2023)
Tanah bagi kehidupan manusia mempunyai kedudukan yang sangat penting. Hal ini disebabkan hampir seluruh aspek kehidupannya terutama bagi bangsa Indonesia tidak dapat terlepas dari keberadaan tanah yang sesungguhnya tidak hanya dapat ditinjau dari aspek ekonomi saja, melainkan meliputi segala kehidupan dan penghidupannya. Tanah mempunyai multiple value, maka sebutan tanah air dan tumpah darah dipergunakan oleh bangsa Indonesia untuk menyebutkan wilayah negara dengan menggambarkan wilayah yang didominasi tanah, air, dan tanah yang berdaulat. Penelitian ini bertujuan untuk mengkaji dan menganalisis penyelesaian sengketa antara masyarakat dengan pemerintah terhadap Kawasan Hutan. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian yuridis normatif yaitu metode penelitian hukum doktrinal dengan cara menelaah dan 6menelaah ketentuan peraturan perundang-undangan yang berlaku sebagai dasar untuk kemudian menganalisa masalah yang diteliti. Berdasarkan hasil penelitian bahwa pentingnya peranan tanah dalam kehidupan manusia, tanah menjadi objek yang rawan terjadi perselisihan atau perselisihan antar manusia, hal ini terjadi karena kebutuhan manusia akan tanah semakin meningkat, tanah dapat menimbulkan gangguan dan melibatkan masyarakat secara luas, sehingga dituntut untuk menanganinya secara tepat. Para pihak yang terlibat dan berwenang untuk menangani persoalan di kawasan hutan masyarakat menyelesaikannya dengan berbagai cara. Metode penyelesaian sengketa yang ditempuh selama ini adalah melalui pengadilan (litigasi). Seiring berjalannya waktu, penyelesaian sengketa melalui musyawarah semakin banyak dilakukan. Sengketa tanah yang lebih banyak menyangkut masalah kepentingan atau kepentingan para pihak relatif lebih mudah diselesaikan melalui musyawarah sepanjang kedua belah pihak saling terbuka dan menginginkan penyelesaian yang terbaik bagi semua pihak.Land for human life has a very important position. This is due to the fact that almost allaspects of life, especially for the Indonesian people, cannot be separated from theexistence of land, which in fact cannot only be viewed from an economic aspect, butcovers all life and livelihoods. Land has multiple values, so the terms homeland andhomeland are used by the Indonesian people to refer to the territory of the country bydescribing areas dominated by sovereign land, water and land. This study aims toexamineandanalyzethesettlementofdisputesbetweenthecommunityandthegovernmentregardingForestAreas.Theresearchmethodusedin thisresearchisnormative juridical research, namely the doctrinal law research method by examiningand studying the provisions of the applicable laws and regulations as a basis for thenanalyzing the problem under study. Based on the results of the study that the importantrole of land in human life, land is an object that is prone to disputes or disputes betweenpeople, this happens because human needs for land are increasing, land can causedisturbancesandinvolvethewidercommunity,sothey arerequiredtohandleitappropriately . The parties involved and authorized to handle problems in communityforest areas solve them in various ways. The dispute resolution method adopted so far isthrough the courts (litigation). Over time, dispute resolution through deliberations isincreasingly being carried out. Land disputes that involve more issues of interest or theinterests of the parties are relatively easier to resolve through deliberations as long asbothpartiesare opentoeachotherandwant the bestsolution forallpartiesLand for human life has a very important position. This is due to the fact that almost allaspects of life, especially for the Indonesian people, cannot be separated from theexistence of land, which in fact cannot only be viewed from an economic aspect, butcovers all life and livelihoods. Land has multiple values, so the terms homeland andhomeland are used by the Indonesian people to refer to the territory of the country bydescribing areas dominated by sovereign land, water and land. This study aims toexamineandanalyzethesettlementofdisputesbetweenthecommunityandthegovernmentregardingForestAreas.Theresearchmethodusedin thisresearchisnormative juridical research, namely the doctrinal law research method by examiningand studying the provisions of the applicable laws and regulations as a basis for thenanalyzing the problem under study. Based on the results of the study that the importantrole of land in human life, land is an object that is prone to disputes or disputes betweenpeople, this happens because human needs for land are increasing, land can causedisturbancesandinvolvethewidercommunity,sothey arerequiredtohandleitappropriately . The parties involved and authorized to handle problems in communityforest areas solve them in various ways. The dispute resolution method adopted so far isthrough the courts (litigation). Over time, dispute resolution through deliberations isincreasingly being carried out. Land disputes that involve more issues of interest or theinterests of the parties are relatively easier to resolve through deliberations as long asbothpartiesare opentoeachotherandwant the bestsolution forallparties.